Heart rate variability in healthy volunteers - Liuzina, Kseniya M.; Shinkevich, Marina V. (Experimental Biology and Biotechnology, 2020)
The research results showed that the vegetative tone of the nervous system in different phases of the menstrual cycle is different. In accordance with changes in heart rate (HRV) indicators, we can talk about the predominance of tone of either the sympathetic or parasympathetic department of the autonomic nervous system in each phase of the cycle, to distinguish subgroups of students by the distribution of the tone of the autonomic nervous system during the cycle. It was possible to isolate those HRV indicators that were changed most synchronously (rhythmogram, histogram, and scatterogram indices). The spectrogram indices are distinguished by the highest asynchrony of changes; therefore, it is not very convenient to analyze changes during a cycle. Autocorrelation indicators reflect the relationship and the predominance of one of the circuits of heart rhythm regulation (central or autonomous). Despite the fact that a certain dynamic of changes can be traced, significant differences were noted only for some indicators in each of the groups. HRV indicators in accordance with the standards given in the literature should be clarified.
Keywords: heart rate variability; electrocardiogram; menstrual cycle